Perancangan dan Implementasi Sistem Smart Air Conditioner Berbasis IoT di Gedung Kampus Dharma Wacana untuk Optimalisasi Energi - Saputri, Tri Aristi; Sutomo, Budi; Hairunnisa, Afifah; Syaputra, M. Adie; Sulistiyanto, Sulistiyanto (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The conventional air conditioning (AC) system utilized in the Dharma Wacana Campus building results in high operational costs. Therefore, this study intends to develop and execute an IoT-based Smart Air Conditioner System to enhance energy efficiency and reduce operational expenses. The research methodology comprises three main stages: (1) System Design, where both hardware and software are developed to monitor and control room temperature and humidity; (2) System Implementation, which involves the installation of sensors and actuators, as well as integration with an IoT platform for remote control; and (3) System Evaluation, where the system's performance is assessed through energy consumption data analysis and user satisfaction surveys. The findings indicate that the IoT-based Smart Air Conditioner System can improve energy efficiency by 15% and reduce operational costs by 20%. The analysis reveals that this system offers advantages regarding energy efficiency and cost savings. However, it also presents challenges, including the need for more complex maintenance and higher initial costs. Consequently, it is recommended to implement this system in other educational buildings. Keywords— Smart Air Conditioner, Energy Efficiency, Internet of Things (IoT), Educational Buildings, AI Based Energy Optimization